Long-term avoidance memory formation is associated with a transient increase in mushroom body synaptic complexes in leaf-cutting ants - Falibene, Agustina; Roces, Flavio; Rössler, Wolfgang (Frontiers in Behavioral Neuroscience, 2015)
Long-term behavioral changes related to learning and experience have been shown to be associated with structural remodeling in the brain. Leaf-cutting ants learn to avoid previously preferred plants after they have proved harmful for their symbiotic fungus, a process that involves long-term olfactory memory. We studied the dynamics of brain microarchitectural changes after long-term olfactory memory formation following avoidance learning in Acromyrmex ambiguus. After performing experiments to control for possible neuronal changes related to age and body size, we quantified synaptic complexes (microglomeruli, MG) in olfactory regions of the mushroom bodies (MB) at different times after learning. Long-term avoidance memory formation was associated with a transient change in MG densities. Two days after learning, MG density was higher than before learning. At days 4 and 15 after learning — when ants still showed plant avoidance — MG densities had decreased to the initial state. The structural reorganization of MG triggered by long-term avoidance memory formation clearly differed from changes promoted by pure exposure to and collection of novel plants with distinct odors. Sensory exposure by the simultaneous collection of several, instead of one, non-harmful plant species resulted in a decrease in MG densities in the olfactory lip. We hypothesize that while sensory exposure leads to MG pruning in the MB olfactory lip, the formation of long-term avoidance memory involves an initial growth of new MG followed by subsequent pruning.